Costs of Transmission Assessment Surveys to Provide Evidence for the Elimination of Lymphatic Filariasis. - Molly A Brady; Rachel Stelmach; Margaret Davide-Smith; Jim Johnson; Bolivar Pou; Joseph Koroma; Kingsley Frimpong; Angela Weaver (PLoS Neglected Tropical Diseases)
Background To reach the global goal of elimination of lymphatic filariasis as a public health problem by 2020, national programs will have to implement a series of transmission assessment surveys (TAS) to determine prevalence of the disease by evaluation unit. It is expected that 4,671 surveys will be required by 2020. Planning in advance for the costs associated with these surveys is essential to ensure that the required resources are available for this essential program activity. Methodology and findings Retrospective cost data was collected from reports from 13 countries which implemented a total of 105 TAS surveys following a standardized World Health Organization (WHO) protocol between 2012 and 2014. The median cost per survey was $21,170 (including the costs for rapid diagnostic tests [RDTs]) and $9,540 excluding those costs. Median cost per cluster sampled (without RDT costs) was $101. Analysis of costs (excluding RDTs) by category showed that the main cost drivers were personnel and travel. Conclusion Transmission assessment surveys are critical to collect evidence to validate elimination of LF as a public health problem. National programs and donors can use the costing results to adequately plan and forecast the resources required to undertake the necessary activities to conduct high-quality transmission assessment surveys.